Republic of Rwanda : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report is an assessment of the corporate sector accounting, financial reporting, and auditing practices within Rwanda. This Report on the Observance of Standards and Codes (ROSC) is benchmarked to International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) and draws on international experience and good practices to assess the strengths and weaknesses of the institutional underpinnings of corporate financial reporting and make policy recommendations. This assessment is mainly aimed at preparing a road map for institutional capacity building including development of the accountancy profession for bolstering the corporate sector accounting, financial reporting, and auditing in Rwanda. Rwanda is making considerable effort to align its accounting and auditing practices with internationally accepted standards and codes. Along with its growing economy, Rwanda must take effective steps for strengthening all the pillars of the infrastructure of accounting and auditing in line with the international good practices. The ROSC review findings reveal that there are varying compliance gaps in both accounting and auditing practices in Rwanda. These gaps stem from lack of clearer understanding among practicing accountants and auditors about the requirements of internationally accepted standards, inadequate technical capacities of the regulators, absence of implementation guidance, lack of independent oversight of the auditing profession, and shortcomings in professional education and training. The Institute of Certified Public Accountants of Rwanda (ICPAR) will assume the role of the self-regulatory professional accountancy body in the country.